Comparison Between Subcutaneous and Intravenous DDAVP in Mild and Moderate Hemophilia A - De Sio, L; Mariani, G; Muzzucconi, M G; Chistolini, A; Tirindelli, M C; Mandelli, F (Thrombosis and Haemostasis, 1985)
Sixteen patients with mild and moderate hemophilia were given Desmopressin (DDAVP) subcutaneously in the absence of any actual bleeding. The response to the drug – in terms of factor VIII coagulant activity rise – became apparent 15 min after the injection, reaching the maximal response after one hour (x̄ 3.2 times the baseline levels; SD 1.21). This response was not different from that elicited using the intravenous route in 18 hemophiliacs of comparable severity after the same time interval. No local or general side-effects were recorded after the subcutaneous administration of DDAVP. We therefore conclude that the subcutaneous route adds further evidence to the reliability of this alternative treatment in mild factor VIII deficiencies, thus making home treatment with this vasopressin analogue possible.
Keywords: DDAVP; Hemophilia A; Mild hemophilia; Subcutaneous DDAVP